The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.21203/rs.3.rs-52587/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Long Non-Coding RNA FOXD1-AS1 Promotes the Progression and Glycolysis of Nasopharyngeal Carcinoma by Sustaining FOXD1 Expression

Abstract: Background: Increasing evidence have emphasized the importance of long non-coding RNAs (lncRNAs) in various human cancers progression. Forkhead box D1 antisense RNA1 (FOXD1-AS1) is a novel lncRNA and plays vital regulatory role in diverse biological processes of cancers. However, the biological function, molecular mechanism and clinical significance of FOXD1-AS1 in nasopharyngeal carcinoma is still unknown.Methods: Comprehensive bioinformatics analysis and qRT-PCR was conducted to detect the expression level o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…Recent studies have demonstrated that upregulated FOXD1 is related to the metastasis status and adverse clinical outcomes of OSCC [ 10 ]. In addition, FOXD1-AS1 can enhance the proliferation and decrease the apoptosis of nasopharyngeal carcinoma by upregulating FOXD1 expression [ 21 ]. These results indicate that FOXD1 can behave as an oncogene in cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated that upregulated FOXD1 is related to the metastasis status and adverse clinical outcomes of OSCC [ 10 ]. In addition, FOXD1-AS1 can enhance the proliferation and decrease the apoptosis of nasopharyngeal carcinoma by upregulating FOXD1 expression [ 21 ]. These results indicate that FOXD1 can behave as an oncogene in cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies demonstrated that upregulated FOXD1 was related to the metastasis status and adverse clinical outcomes of oral squamous cell carcinoma [10]. Besides, FOXD1-AS1 could enhance the proliferation and decrease the apoptosis of nasopharyngeal carcinoma by upregulating FOXD1 expression [21]. These results indicate that FOXD1 can behave as an oncogene in cancer.…”
Section: Discussionmentioning
confidence: 84%
“…In recent years, accumulating evidence has revealed fundamental roles of lncRNAs in the regulation of numerous physiological and pathological processes, such as cell differentiation, proliferation and apoptosis, and the initiation and progression of human cancer. 7 , 15 , 16 At present, it is widely acknowledged that numerous lncRNAs are involved the progression of NSCLC. For example, long noncoding RNA KCNMB2-AS1 increased ROCK1 expression by Sponging microRNA-374a-3p to facilitate the progression of NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Emerging researches have suggested that lncRNAs serve crucial functions in the initiation and development of human cancer. 7,8 Numerous studies have demonstrated that lncRNAs were involved in NSCLC progression. 9,10 LncRNA PCAT18 was a recently identified lncRNA.…”
Section: Introductionmentioning
confidence: 99%